Polarizing without legitimizing: The effect of lead candidates' campaigns on perceptions of the EU democracy. (December 2016) - Popa, Sebastian Adrian; Rohrschneider, Robert; Schmitt, Hermann
Abstract: Has the presence of Spitzenkandidaten —"lead-candidates"—in the 2014 European parliamentary election mobilized citizens in support of the EU? A core goal of this innovation was to bring the EU closer to its citizens and to boost turnout. We therefore examine how the presence of leading candidates affects perceptions of the EU democracy. Contrary to what innovators had hoped for, we find that the presence of lead candidates has polarized the European public. Those who support the EU believe the EU has become more democratic as a result of the leading candidates. But those who generally view the EU skeptically oppose it even more when they are aware of the presence of pro-EU candidates.